Dragons and marshmallows - Citro, Asia; Lindsay, Marion (Woodinville, WA : The Innovation Press, 2017)
A girl, Zoey, and her cat, Sassafras, use science experiments to help a dragon with a problem.
School Library Journal, January 2017
Kirkus Review, January 2017
3.1
K-3
640L
N
Keywords: Dragons -- Fiction; Marshmallow -- Fiction; Science -- Experiments -- Fiction